PREVALENSI KOLIBASILOSIS PADA AYAM BROILER YANG DIINFEKSI Escherichia coli DENGAN PEMBERIAN BIOADITIF, PROBIOTIK, DAN ANTIBIOTIK - Ade Erma Suryani; Mohammad Faiz Karimy; Lusty Istiqomah; Ahmad Sofyan; Hendra Herdian; Michael Haryadi Wibowo (Pusbindiklat - LIPI, 2014)
The purpose of this research was to study the efficacy of bio-additive (a mixture of Lumbricus rubellus meal extract, Morinda citrifolia leaf extract and lactic acid bacteria ), probiotics, and antibiotics on the prevalence co- libacillosis and healthy status of broiler that infected by E. coli strain Avian Pathogenic Escherichia coli (APEC). A total of 140 DOC were distribute randomly into 20 units of cage, each filled with 7 chickens were arranged in a completely randomized desig . Twenty cages were divided into 5 group , each treatment consisted of 4 replicates. The treatment group consisted of treatment A = infection of E. coli positive control), B = infection of E. coli + bio- additiv , C = infection of E. coli + probiotic , D = infection of E. coli + antibiotic , E = no E. coli infection negative contro). Feed base on corn- soybean is formulated as a basal fee . The experiments were conducted for 35 days, on day 21 chickens infected E. coli. ND vaccination is given at the age of four days and 15 days. The observed parameters were changes of macroscopic, isolation and identification of E. coli, changes in histopathology, blood profiles and antibody titer against ND. Results showed the prevalence colibasillosis on treatment B resulted in the lowest rate (33.3), results in the isolation and identification of chicken with positive clinical symptoms kolibasilosis infected APEC, and microscopic observations showed histopathological changes in the organs pancreas, heart, liver, and exchanges fabrisius lung. The results of the blood profile analysis showed the presence of the body’s defense mechanism against bacterial infectio , which is evident from the number of leukocytes in treatment A and C are higher tha treatment E (P> 0.0 ), red cell count treatment D higher than E treatment (P> 0.0 ), and total of Hb treatment A higher than treatment E P> 0.0 ). Based on the overall health status, it can be concluded that the administration of bioaditif decrease the prevalence o colibasillosis 67.7 % .